The Physical Activity Environment Policy Index for monitoring government policies and actions to improve physical activity - Woods, Catherine B.; Kelly, Liam; Volf, Kevin; Gelius, Peter; Messing, Sven; Forberger, Sarah; Lakerveld, Jeroen; Den Braver, Nicolette R.; Zukowska, Joanna; Garcia Bengoechea, Enrique (European Journal of Public Health, 2022)
Background A multifaceted response, including government action, is essential to improve population levels of physical activity (PA). This article describes the development process of the ‘Physical Activity Environment Policy Index’ (PA-EPI) monitoring framework, a tool to assess government policies and actions for creating a healthy PA environment. Methods An iterative process was undertaken. This involved a review of policy documents from authoritative organizations, a PA policy audit of four European countries, and a systematic review of scientific literature. This was followed by an online consultation with academic experts (N = 101; 20 countries, 72% response rate), and policymakers (N = 40, 4 EU countries). During this process, consensus workshops were conducted, where quantitative and qualitative data, alongside theoretical and pragmatic considerations, were used to inform PA-EPI development. Results The PA-EPI is conceptualized as a two-component ‘policy’ and ‘infrastructure support’ framework. The two-components comprise eight policy and seven infrastructure support domains. The policy domains are education, transport, urban design, healthcare, public education (including mass media), sport-for-all, workplaces and community. The infrastructure support domains are leadership, governance, monitoring and intelligence, funding and resources, platforms for interaction, workforce development and health-in-all-policies. Forty-five ‘good practice statements’ or indicators of ideal good practice within each domain conclude the PA-EPI. A potential eight-step process for conducting the PA-EPI is described. Conclusions Once pre-tested and piloted in several countries of various sizes and income levels, the PA-EPI good practice statements will evolve into benchmarks established by governments at the forefront of creating and implementing policies to address inactivity.<br